2006
DOI: 10.1007/s11250-006-4437-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect following intranasal exposure of goats to live Pasteurella multocida B:2

Abstract: This study aimed to determine the effect of intranasal exposure to low doses of Pasteurella multocida B:2 on survival of goats challenged with high doses of the same organism. Eighteen goats were selected and divided into three groups. Goats of group 1 were exposed intranasally twice, with a two-week interval, to 7 x 10(6) cfu/ml of live P. multocida B:2. Goats of group 2 were not exposed to P. multocida B:2 but were kept together with the exposed group 1. Goats of group 3 remained as unexposed controls and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Upon arrival at the experimental house, anthelmintic (Ivomectin) was administered subcutaneously at the rate of 0.2mg/kg body weight for three consecutive days. Concurrently, deep nasal swabs were collected weekly for six (6) weeks and examined for the presence of P. multocida by bacterial isolation and polymerase chain reaction (Townsend et al, 1998;Zamri-Saad et al, 2006) to ensure the calves were free from P. multocida prior to start of the experiment. All calves were observed daily while temperature and respiratory rate were monitored.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon arrival at the experimental house, anthelmintic (Ivomectin) was administered subcutaneously at the rate of 0.2mg/kg body weight for three consecutive days. Concurrently, deep nasal swabs were collected weekly for six (6) weeks and examined for the presence of P. multocida by bacterial isolation and polymerase chain reaction (Townsend et al, 1998;Zamri-Saad et al, 2006) to ensure the calves were free from P. multocida prior to start of the experiment. All calves were observed daily while temperature and respiratory rate were monitored.…”
Section: Animalsmentioning
confidence: 99%
“…A stock culture of P. multocida serotype B:2 isolated from a bovine case of HS (local laboratory source) was used (Zamri-Saad et al, 2006). The organism was cultured on blood agar at 37 0 C for 24 h before the brain heart infusion broth was seeded with four uniformly sized colonies and incubated, with shaking for 18 h. The bacterial concentration was determined using the method described by Alcamo (1997) to produce an estimated infection dose of 10 9 colony forming units (cfu)/mL of P. multocida B:2.…”
Section: Inocula Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…During a bacterial infection, haematological and biochemistry changes are first detected during routine blood sampling. However, animal's defence mechanism can react quite differently and there is no singular pattern in complete blood count that indicates a bacterial infection (Weiss and Wardrop, 2010). Jesse et al (2013c) had reported that there were some haematological and biochemical markers that can be used for early detection in animals infected with wild type of Pasteurella multocida.…”
Section: Haematology and Biochemistrymentioning
confidence: 99%
“…Stress in animals will suppress the antibody production which will cause latent carrier to become an active carrier (DeAlwis, 1999). Another study was conducted by Zamri-saad et al (2006), to determine the effect of intranasal exposure to low doses of Pasteurella multocida B2 stimulating antibody production against higher doses of the same organism. In this experiment, all goats showed low antibody response against Pasteurella multocida prior to intranasal exposure.…”
Section: Antibodymentioning
confidence: 99%